2012
DOI: 10.1007/s10552-012-9973-2
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer incidence in Mongolia

Abstract: Purpose Data on international variation in breast cancer incidence may help to identify additional risk factors. Substantially lower breast cancer rates in Asia than in North America and Western Europe are established, but differences within Asia have been largely ignored despite heterogeneity in lifestyles and environments. Mongolia’s breast cancer experience is of interest because of its shared genetics but vastly different diet compared with other parts of Asia. Methods Age-standardized breast cancer inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 26 publications
2
27
1
Order By: Relevance
“…2,12,29 A review of 190 symptomatic PMs by Komninos et al showed that in 83 (43.7%) cases the primary tumor was latent when the PM was discovered. 16 This figure might be influenced by the multiple reports describing rare presentations.…”
Section: Clinical Features Of Pmsmentioning
confidence: 99%
“…2,12,29 A review of 190 symptomatic PMs by Komninos et al showed that in 83 (43.7%) cases the primary tumor was latent when the PM was discovered. 16 This figure might be influenced by the multiple reports describing rare presentations.…”
Section: Clinical Features Of Pmsmentioning
confidence: 99%
“…The incidence rate of this disease vary around the world. For example, the age-standardized incidence rates per 100,000 are: North America 126 (Toriola and Colditz, 2013); Taiwan 81.36 ; Singapur 54.9, Malaysia 39.3 (Sulaiman et al, 2011); Poland 44.5 (Bruzewicz, 2008); Russia 43.2, Japan 42.7, China 21.6, Mongolia 8.0 (Troisi et al, 2012); Saudi Arabia 11.4 (Amin et al, 2014). According to the analysis of trends in the breast cancer incidence and mortality in USA, carried out by Toriola and Colditz (2013) over the past 70 years, the stable incidence rates are monitored after 2003 (126 per 100,000).…”
Section: Introductionmentioning
confidence: 99%
“…BC occurs mainly in women (WHO, 2013) one out of every 10 cases is BC (Varughese et al, 2015). The age standardized incidence rate of the disease is as follows: North America, 126 (Toriola et al, 2013), Turkey 35.8 (Kayhan et al, 2014) and Russia 43.2 (Troisi et al, 2012) per 100, 000 people. Breast cancer is the most commonly diagnosed type of cancer and the second leading cause of cancer related death among women (Yilmaz and Arslan, 2015).…”
Section: Introductionmentioning
confidence: 99%